If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.60x + 0.60(60) = 0.30(118) Multiply 0.60 * 60 0.60x + 36 = 0.30(118) Reorder the terms: 36 + 0.60x = 0.30(118) Multiply 0.30 * 118 36 + 0.60x = 35.4 Solving 36 + 0.60x = 35.4 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-36' to each side of the equation. 36 + -36 + 0.60x = 35.4 + -36 Combine like terms: 36 + -36 = 0 0 + 0.60x = 35.4 + -36 0.60x = 35.4 + -36 Combine like terms: 35.4 + -36 = -0.6 0.60x = -0.6 Divide each side by '0.60'. x = -1 Simplifying x = -1
| -9.2(x-3.5)=36.8 | | 2x^2+x^3y^4=1 | | 4(x-8)+7=11x-15 | | 3(6x+7)-9=18x+12 | | 3(1-5x)=x+19 | | 3r+2s-4t=-24 | | 11x-7x=36 | | 8x+4=x+20 | | 72d-45+13=12d-2 | | 91x^3+8x+9x^2= | | 2b+3+2(2b+3)+3(2b+3)=477 | | .1(x+11)=-2(8-x) | | -2y+2=-2(3y+17) | | 11-x/4=2-x | | 84=(2w+2)w | | 5B-52=93 | | m^2+4m+4= | | 10-x-3=5x-13-4x | | 6(5x+6)=1-5x | | x^2=2.89 | | 13.50+74=85.7 | | -8x=-2x+4x | | 15x+0.5=25x+0.25 | | 3y^4-(4y^4+3)= | | 7b-9=5b+13 | | 45p=180 | | 3c(4c+6)-18=168 | | 5(8+9d)=-21 | | 3(6x-12)=2x+44 | | 8x-5x=33 | | 11(y-3)=7(2-3h) | | 6k-3(k-8)=162 |